2014
DOI: 10.1007/s00277-014-2031-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin retains independent prognostic significance in diffuse large B-cell lymphoma in the post-rituximab era

Abstract: Serum albumin (SA) has been shown to be a prognostic marker in many hematological malignancies and in diffuse large B-cell lymphoma (DLBCL) prior to chemo-immunotherapy. SA may be a surrogate for age, comorbid status, and disease severity. Here, we aimed to assess whether SA can be an independent prognostic marker in patients with newly diagnosed DLBCL treated with rituximab, cyclophosphamide, vincristine, doxorubicin, and prednisone (R-CHOP). Patients who presented at the Moffitt Cancer Center from 2007 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 38 publications
4
54
1
2
Order By: Relevance
“…A recently published paper found that an albumin level of <3.7 g/dl is an independent prognostic indicator in DLBCL patients treated with R‐CHOP . They found that serum albumin <3.7 g/dl significantly reduced OS and PFS in the good and poor prognostic category . Although, surprisingly, in our study pretreatment hypoalbuminemia was associated with decreased OS, it was not associated with response rate.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…A recently published paper found that an albumin level of <3.7 g/dl is an independent prognostic indicator in DLBCL patients treated with R‐CHOP . They found that serum albumin <3.7 g/dl significantly reduced OS and PFS in the good and poor prognostic category . Although, surprisingly, in our study pretreatment hypoalbuminemia was associated with decreased OS, it was not associated with response rate.…”
Section: Discussioncontrasting
confidence: 67%
“…Studies of non‐Hodgkin's lymphoma reported that albumin <3.0 g/dl was one of the factors predicting early death from aggressive disease treated with ACVBP (doxorubicin, cyclophosphamide, vindesine, bleomycin, and prednisone) . A recently published paper found that an albumin level of <3.7 g/dl is an independent prognostic indicator in DLBCL patients treated with R‐CHOP . They found that serum albumin <3.7 g/dl significantly reduced OS and PFS in the good and poor prognostic category .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a variety of systemic inflammatory biomarkers has been identified and studied in patients with DLBCL, and might provide useful prognostic information (Table 4). These biomarkers include NLR [30,31], serum LDH [32], serum CRP [33,34], GPS [35,36], serum albumin [37,38], and the peripheral blood absolute lymphocyte and monocyte counts [39]. Troppan et al [30 ]reported that DLBCL patients with an NLR score <4 at diagnosis experienced better OS and disease-free survival than patients with a score of ≥4.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found that the prognostic value of sarcopenia was limited in elderly and male patients [28,29]. There are also contradictory reports regarding the prognostic role of hypoalbuminemia with various cut-off points [13,16,30].…”
Section: Discussionmentioning
confidence: 99%
“…Given the high tumor burden of DLBCL and the favorable response rate with substantial treatment-related toxicities of R-CHOP treatment, the prognostic role of cancer cachexia is also likely to be observed in DLBCL patients. Several markers for malnutrition and cachexia such as body mass index (BMI), sarcopenia, adipopenia, and serum albumin level have been studied and suggested to be prognostic factors in DLBCL [13][14][15][16]. Additionally, the clinical value of the Geriatric Nutritional Risk Index (GNRI), which was originally developed to predict nutrition-related morbidity and mortality in non-cancer patients [17], was evaluated in two previous DLBCL studies with conflicting results [18,19].…”
Section: Introductionmentioning
confidence: 99%